The activity-based costing method and its impact on price setting in agro-industrial wine companies - Guillermo Vega, Leticia Ruth (2020)
The objective of this study was to determine whether the implementation of an activity-based costing method has an impact on price setting in agro-industrial wine companies in Tacna province. In order to implement this method, the winemaking process was broken down into activities, and cost drivers were determined, which were assigned according to the level of resource use per activity. The implementation of this method showed greater accuracy and efficiency in the allocation of production costs, by identifying the most expensive and the most economical variety of wine, favoring the reduction of costs, was effective and personalized to determine the profit margin by variety of wine, consequently, influenced the setting of the price as it was more competitive, real and differentiated by product. In contrast to the traditional system, which provided distorted results, by making an erroneous distribution of the cost based on the volume of production, it was inaccurate in processes with different varieties of wine, which generated considerable differences in costs